UTILIZING THE CAPACITY OF POSITIVE PEER PRESSURE THROUGH THE GLOBAL YOUTH JUSTICE MOVEMENT: A ‘GOLDEN’ OPPORTUNITY FOR THE BALKANS - Winterdyk, John (NBP. Nauka, bezbednost, policija, 2017)
The predicament of juvenile delinquency for most nations, including that of the Balkan region at large, has been something of an enigma ever since juvenile justice legislation was first introduced. In recent years, juvenile delinquency in the Balkans has not only been increasing but its gravity has also trended upward and added to the burden of a strained juvenile justice system. This article presents an alternative option to the formal juvenile justice system which is designed to empower youth, builds community capacity and youth resiliency, and is reintegrative and restorative in nature. An overview of the peer court model is presented and described within a possible Balkan context. Various evidence is discussed as to its relative success in other regions of the world. The paper concludes with several observations as to why the peer court model could/should be adopted by countries in the Balkans along with several pragmatic and practical considerations around the implementation and administration of the model.